Analysis Of Information Security It Governance With Cobit 5 Framework At PT. Indonesia Comnets Plus (ICON+) SUMBAGUT - Ananda Salsabila Khairi; Putrawan Putrawan; Rafli Khalis Nugraha; Ali Ikhwan (LPPM Universitas Dharma Andalas, 2023)
Currently, information technology is an important part for companies to meet their needs and support the achievement of corporate strategy. Providing a competitive advantage, increasing effectiveness, time and reducing costs is the role of information technology in today's business area. As well as information is an important asset for the company that helps in the development of the company. Information really needs to be guarded and managed securely. PT. ICON+ prioritizes information technology in daily activities, so PT. ICON+ also needs to secure the information assets that exist in the company. Information security must be maintained because it is an important asset owned by the company. Therefore, examining information technology governance and information security using COBIT 5 in a company is really needed. This research can find out whether the company has fulfilled the indicator requirements or not otherwise. The framework and maintenance governance audit was carried out at PT. ICON+ is used to find out indicators of ability. The results were obtained using a questionnaire distributed to companies. In this study, it was found that PT. ICON+ achieved the expected result.